Term Premia and Inflation Uncertainty: Empirical Evidence from an International Panel Dataset - Wright, Jonathan H (American Economic Review, 2011)
This paper provides cross-country empirical evidence on term premia. I construct a panel of zero-coupon nominal government bond yields spanning ten industrialized countries and nearly two decades. I hence compute forward rates and use two different methods to decompose these forward rates into expected future short-term interest rates and term premiums. The first method uses an affine term structure model with macroeconomic variables as unspanned risk factors; the second method uses surveys. I find that term premiums declined internationally over the sample period, especially in countries that apparently reduced inflation uncertainty by making substantial changes in their monetary policy frameworks. (JEL E13, E43, E52, G12, H63)